ANALYSIS OF CODE MIXING IN FACEBOOK SOCIAL MEDIA BY CULINARY STUDENT AT MONARCH GIANYAR COLLEGE - I Gusti Ayu Winda Yuliantari; N. M. A. Yuliastini; I. M. M. Valentine (Lingua Scientia, 2020)
AbstractThis research is aimed to describe the use of code mixing in social media Facebook by culinary students of Monarch Gianyar College. Social media especially Facebook is considered as one of online social media of communication that used by people especially student. Facebook has become the most popular social media and many people had spends much time using Facebook. Based on that reason, the researcher would intend to explore in how student do code mixing in social media especially Facebook and the reason behind it. In this research, the indicator form of the researcher used in code mixing are words, phrases, reduplication, idioms, and hybrids. This research use quantitative descriptive method. The researcher instrument that used is in form of observation, note taking and documentation. The result shows that there are 165 and 35 kind of code mixing in Facebook timeline and comment based on categories of code mixing which classified into several form such as forms of words, phrases, reduplication, idioms, and hybridsKeywords : code-switching, facebook platform